2018
DOI: 10.1007/s12016-018-8690-3
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and Immunologic Perspectives of Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic immune-mediated inflammatory condition primarily involving the gastrointestinal tract. It includes Crohn's disease (CD), ulcerative colitis (UC), and a less common phenotype-indeterminate colitis. It is thought to result from a complex interplay of environmental, microbial, and host factors including genetic factors, although the exact mechanism is not known. Dietary factors have been shown to play a role in the pathogenesis of IBD and can potentially alter the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 152 publications
0
15
0
Order By: Relevance
“…Oat β-glucan 94% fermentation products led to a higher increase of cytokines and chemokines compared to oat β-glucan 28% fermentation products, suggesting that metabolites from oat β-glucan fermentation play an important role in modulating cytokine and chemokine productions. It is widely accepted that pro- and anti-inflammatory signals are both important for a balanced immune response ( Buckley & Rast, 2017 ; Clarke & Chintanaboina, 2018 ; Koboziev et al, 2015 ; Kotredes, Thomas & Gamero, 2017 ; Martin-Subero et al, 2016 ; Pott & Stockinger, 2017 ; Sarrabayrouse et al, 2015 ; Webb & Tait Wojno, 2017 ). Even if the modulated cytokines may exert both pro- and anti-inflammatory properties, our results clearly show that their expression is highly regulated by the fermentation supernatant of oat β-glucan 28% and oat β-glucan 94% in two of three donors.…”
Section: Discussionmentioning
confidence: 99%
“…Oat β-glucan 94% fermentation products led to a higher increase of cytokines and chemokines compared to oat β-glucan 28% fermentation products, suggesting that metabolites from oat β-glucan fermentation play an important role in modulating cytokine and chemokine productions. It is widely accepted that pro- and anti-inflammatory signals are both important for a balanced immune response ( Buckley & Rast, 2017 ; Clarke & Chintanaboina, 2018 ; Koboziev et al, 2015 ; Kotredes, Thomas & Gamero, 2017 ; Martin-Subero et al, 2016 ; Pott & Stockinger, 2017 ; Sarrabayrouse et al, 2015 ; Webb & Tait Wojno, 2017 ). Even if the modulated cytokines may exert both pro- and anti-inflammatory properties, our results clearly show that their expression is highly regulated by the fermentation supernatant of oat β-glucan 28% and oat β-glucan 94% in two of three donors.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is a chronic immune system-mediated inflammatory disorder that comprises a range of conditions predominantly affecting the gastrointestinal tract [ 1 ]. These conditions include Crohn's disease, ulcerative colitis, and indeterminate colitis, a rare condition.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that Farrerol significantly improved the expression of claudin-1, occludin, and ZO-1 in colonic tissue from TNBS-induced mice. The mucus layer is mostly composed of mucin, defensin, and lecithin that is abundant in the colon and covers the outer epithelial surface to protect the mucosa [ 41 ]. The mucus layer contains an outer loose permeable layer that contacts commensal bacterial and an inner firm mucus layer that contacts the intestinal epithelium cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%